Macro- and micro-morphometrical seed characters in seven species of Egyptian Datura and Nicotiana (Solanaceae) - Barakat, Nasser A.m.; M.s.a., Soliman; Zahran, Fatma A. (Phytotaxa, 2019)
This work describes and compares the external macro- and micro-morphometrical features of the seed of seven species of Datura and Nicotiana belonging to two tribes of the Solanaceae. Fourteen unique characters were measured and described, the results of which reveal marked differences, both among and within genera. The species of Datura exhibited higher values than those of Nicotiana in all morphometrically measured parameters, such as seed weight, size, perimeter, and surface area, with no or little variation in roundness and eccentricity. For qualitative features, the notched outline, rough texture, pitted ornamentation, circular hilum shape, and stellate coat pattern characterized all examined species of Nicotiana. The yellow colour of the seeds can be used to distinguish the seeds of Nicotiana glauca from the brown seeds of other Nicotiana species examined in this study. The circular shape of the hilum distinguishes the seeds of Datura innoxia from those of Datura metel, which have oral-shaped hilum. Considerable differences in seed coat morphology were found both among and within species. However, the size and shape of the seed can be useful and stable characters, and the position of the hilum had some taxonomic significance.